Selected Decisions and Selected Documents of the International Monetary Fund 21st issue - International Monetary Fund; International Monetary Fund. (Washington, D.C : International Monetary Fund, 1996)
This volume includes decisions, interpretations, and resolutions of the executive Board and the Board of governors of the International Monetary Fund, as well as selected documents, to which frequent reference is made in the current activities of the Fund. It includes certain documents relating to the Fund, the United Nations and other international organizations..
Includes index
osa 17/09/13, gau 02/08/16 , jus 04/08/21
Ref.
Keywords: International Monetary Fund; International finance